2(1+k)+10=2(k+6)

Simple and best practice solution for 2(1+k)+10=2(k+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(1+k)+10=2(k+6) equation:



2(1+k)+10=2(k+6)
We move all terms to the left:
2(1+k)+10-(2(k+6))=0
We add all the numbers together, and all the variables
2(k+1)-(2(k+6))+10=0
We multiply parentheses
2k-(2(k+6))+2+10=0
We calculate terms in parentheses: -(2(k+6)), so:
2(k+6)
We multiply parentheses
2k+12
Back to the equation:
-(2k+12)
We add all the numbers together, and all the variables
2k-(2k+12)+12=0
We get rid of parentheses
2k-2k-12+12=0
We add all the numbers together, and all the variables
=0
k=0/1
k=0

See similar equations:

| -50=4-6v | | 12-8x=(x+4) | | 6m=24.6 | | 5^x+3=3 | | 7(n-3)=7 | | -2*x-7=-16 | | (1/14)x+x=180 | | –2.3f=9.2 | | M7=4x+15 | | h-0.43=0.37 | | 5(r+2)=2r+10 | | 1x+51=17 | | 10x-5=3x+36 | | 8=4(c+5) | | 54x+6=90 | | 45w+123.96=753.95 | | -65=8v-9 | | 5x-7)(3x-4)=180 | | -6a-5=-59 | | -(7x+4)-2x-(3x-9)=-8 | | 5x-7)(3x-4)=1180 | | 7(6x-2)=112 | | p=34100(1+.04)^3 | | x-4.40=4.75 | | 43=(x+3) | | 0=(9k-⅔)+33 | | 1000-n=456 | | 2=v/8-2 | | -m-(4m-2)=2-5m | | 5x-7)(3x-4)=13+2 | | 12(18-5x)=16(6-4x) | | 4x+4=456 |

Equations solver categories